Optimized semi-chemical pulping of Arundo donax L. biomass: Correlating chemo-mechanical pretreatment with fiber morphology and paper strength - Peng Yu; Liqin Liu; Xiaofeng Lyu; Yinying Long; Shaodong Song; Jianhua Zhao; Bin Lu; Qingliang Xu; Zhengbai Cheng; Hongbin Liu; Xingye An (Biomass and Bioenergy, 2026)

Reinforcement learning enhanced zeroth-order optimization for large-scale multiobjective optimization problems - Yonglin He; Cheng He; Zhichao Lu; Ye Tian; Handing Wang; Yinglan Feng; Hongbin Li (Swarm and Evolutionary Computation, 2026)

Macrophyte-to-algae transition: Suspended particulate matter mediates the bioavailability and retention of heavy metal(loid)s in the sediment - Wenxuan Han; Yiheng Du; Xue Sun; Zhaode Wang; Lei Zhang; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Journal of Environmental Chemical Engineering, 2026)

High energy density and power density foam nickel-loaded 3D chromium-doped carbon nanosheet supercapacitor electrodes - Jianglong Cheng; Yaru Li; Baosen Mi; Quan Wang; Hongbin Wang; Tao Zhou; Haipeng Hou; Yumeng Zhu (Fuel, 2026)

Delocalized-electron engineered 2D mesoporous COFs boosting interfacial desolvation toward low-temperature zinc metal batteries - Yidan Duan; Yongzheng Zhang; Zhiyan Wang; Yue Liu; Rui Han; Cheng Ma; Duan Bin; Hongbin Lu; Wenming Qiao; Jitong Wang; Licheng Ling (Chemical Engineering Journal, 2026)

Visual Perception and Gamma Oscillations in Cat V1 are Dynamically Correlated in Contrast Sensitivity Functions - Zheng Ye; Jian Ding; Changning Cheng; Hao Yu; Fei Xu; Qingyan Sun; Hongbin Yang; Tianmiao Hua; Hao Wang (Neuroscience Bulletin, 2026)

Lignin-mediated synthesis of morphology-controllable Ag@AgCl@LS nanofillers as high sensing and anchored joints for advanced hydrogel-based instruction & fingertip sensors - Jian Yang; Lingyu Yin; Xingye An; Kang Yang; Liqin Liu; Zhengbai Cheng; Hongbin Liu; Liang He; Yonghao Ni (Chemical Engineering Journal, 2026)

Carbon footprint management and net-zero strategies for bleached kraft bamboo pulps under forestry-pulp-paper integration - Jiayi Song; Liqin Liu; Xiaofeng Lyu; Biao Xia; Zhengbai Cheng; Bin Lu; Qingliang Xu; Hongbin Liu; Xingye An (Journal of Environmental Management, 2026)

Identification of drought-tolerant mung bean varieties based on germination, antioxidant, and osmolyte profiles - Ziyu Zhang; Cheng Qin; Li Li; Jie Shen; Hongbin Pei; Zeyan Zhang; Hongbing Li; Qiang Li; Huida Lian (Protoplasma, 2026)

Organic matter cycling reveals escalating algal blooms and accelerated mineralization in a macrophyte-dominated cold-arid eutrophic lake - Fengrui Zhang; Wenxuan Han; Xue Sun; Zhaode Wang; Lei Zhang; Qiushi Shen; Haijin Lan; Bingfa Chen; Hongbin Yin; Cheng Liu (Water Research, 2026)

Global lysine crotonylation profiling reveals metabolic and stress-responsive mechanisms in Reynoutria japonica - Lei You; Peng Zhang; Hongbin Cheng; Yujie Deng; Haitang Xiong; Jumei Zhang; Zhengxiu Ye; Zezhi Zhang; Chen Li; Victor Manuel Martinez Espinosa; Chao Zhou; Lanlan Zheng; et al. (Journal of Plant Physiology, 2026)

High-throughput phytoplankton monitoring and screening of harmful and bloom-forming algae in coastal waters with updated functional screening database - Linus Shing Him Lo; Hongbin Liu; Jian-Wen Qiu; Po Keung Eric Tsang; Zhijun Dai; Jinping Cheng (Marine Pollution Bulletin, 2026)

Radical-Net: A chemistry-enhanced transformer for elementary radical reactions in pollutant chemistry - Zhi Huang; Jiang Yu; Wei He; Pengxinyue Huang; Siwei Deng; Hongbin Jiang; Jie Yu; Chun Yang; Cheng Han; Yinying Jiang; Weiwei Zhu; Yucheng Liu (Journal of Hazardous Materials, 2026)

Identification of seed maize fields from hyperspectral imagery by fusion of spectral and spatial features - Jinpeng Cheng; Hao Yang; Xiaoyu Cao; Qiang Wu; Na Zhang; Zhiyu Yan; Hongbin Wang; Linsheng Huang; Xinming Ma; Shuping Xiong; Guijun Yang (Computers and Electronics in Agriculture, 2025)

Sustainable renewable ammonia production via solar-driven biomass gasification: a techno-economic perspective - Hongbin Wan; Jingang Yao; Guanyi Chen; Beibei Yan; Zhanjun Cheng; Weiming Yi; Jian Li; Lingyu Tai; Obie Farobie; Paolo De Filippis; Benedetta De Caprariis (Chemical Engineering Journal, 2025)

Synergy of algal particle deposition and bioturbation amplifies the internal phosphorus loading - Fengrui Zhang; Lixian Tan; Wenxuan Han; Lei Zhang; Qiushi Shen; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Water Research, 2025)

Study on the effects of high temperature on autophagy and apoptosis in different organs of Bombyx mori based on calcium ion homeostasis - Peilin Peng; Hongbin Zou; Jialu Cheng; Haoyi Gu; Guimin Nong; Xuelin Qin; Bing Li (Insect Biochemistry and Molecular Biology, 2025)

Using speleothem 87Sr/86Sr variations tracking the controls on trace element (Sr-Mg) compositions - Rishui Chen; Shuyu Xue; Hongbin Zhang; Michael Griffiths; Yi Zhou; Xing Liu; Zhenli Zhu; Lin Chen; Wei Guo; Shitou Wu; Hai Cheng; Junhua Huang; et al. (Global and Planetary Change, 2025)

Synergistic effect of charge-transfer bridge and surface defects for highly efficient photothermal catalytic CO2 reduction over 2D/3D SrTiO3/Zn0.5Cd0.5S - Peigen Ding; Zhanfei Fu; Liuna Zhang; Hongbin He; Jiarui Yang; Qi He; Zesheng Li; Jiale Cheng; Tian Gao; Xiaoming Gao (Chemical Engineering Journal, 2025)

Terracing stabilizes and enhances soil organic carbon sequestration benefits of revegetation on the Loess Plateau, China - Hui Cheng; Hao Feng; Xiaoping Zhang; Zhiguang Li; Kaiyang Yu; Hongbin Ma; Jia Xu (CATENA, 2025)

Capillarity effect on groundwater dynamics during periodic forcing - Dawei Cheng; Hongbin Zhan; Xi Chen; Shengke Yang; Dongyong Sun; Xiuyu Liang (Journal of Hydrology, 2025)

The mechanism of high-concentration florfenicol exposure inducing apoptosis in the midgut of Bombyx mori (Lepidoptera: Bombycidae) - Chao Tian; Jialu Cheng; Haoyi Gu; Hongbin Zou; Peilin Peng; Bing Li (Journal of Asia-Pacific Entomology, 2025)

The importance of interface interactions in flexible sensing materials: classification, effect, and application - Fei Chen; Fangcheng Qiu; Xiucun Li; Yufeng Song; Xiao Liu; Hong Jiang; Hongbin Liu; Yonghao Xiao; Meng Gao; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2025)

Crack propagation controlling via sliding cyclodextrin for high-density sensor array - Xin Xu; Shize Fang; Zijun Xu; Mengqi Zhang; Yufeng Song; Fangcheng Qiu; Yang Liu; Bowen Cheng; Hongbin Liu; Yonghao Ni (Chemical Engineering Journal, 2025)

Research on magnetron sputtering thin films as electrode materials for supercapacitors - Jianglong Cheng; Baosen Mi; Quan Wang; Hongbin Wang; Tao Zhou; Yaru Li; Haipeng Hou; Yumeng Zhu (Chemical Engineering Journal, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

Dual targeting of FR+CD44 overexpressing tumors by self-assembled nanoparticles quantitatively conjugating folic acid-hyaluronic acid to the GSH-sensitively modified podophyllotoxin - Chaozheng Zhang; Yao Chen; Yi Zuo; Maolin Wang; Hongyu Chen; Chuanqi Wang; Yuening Cao; Yingjie Zeng; Ying Chen; Tingting Zhang; Xian Ge; Xiujun Cao; et al. (Chemical Engineering Journal, 2025)

Negative emotional eating patterns in Chinese adolescents: A replication and longitudinal extension with latent profile and transition analyses - Hongbin Weng; Wesley R. Barnhart; Hana F. Zickgraf; Urvashi Dixit; Yawei Cheng; Gui Chen; Jinbo He (Appetite, 2025)

Corrigendum to “Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis” [Chem. Eng. J. 482 (2024) 148815] - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

Promoting photothermal catalytic N2 reduction through dynamic mass transfer and accelerated charge transfer dynamics - Tianxu Zeng; Hongbin He; Kangjie Cheng; Yanan Hu; Peigen Ding; Liuna Zhang; Xiaoming Gao (Chemical Engineering Journal, 2024)

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

Ship Optimization Based on Fully-Parametric Models for Hull, Propeller and Rudder - Xuankai Cheng; Xinhui Huang; Detao Xu; Zhengbin Zhao; Hongbin Liu; Ming Kong; Renwei Ji (Journal of Marine Science and Engineering, 2024)
The purpose of ship optimization is to reduce the resistance of the ship and improve the propulsive efficiency of the propeller. Taking the design of the hull, propeller and rudder as an example, the integration optimization of ship speed performance based on the fully-parametric model was described in detail. Based on the parent hull, stock propeller and flat plate rudder, the fully-parametric coupling models of ship, propeller and rudder were established. The fully-parametric optimization method was used to optimize the optimal combination of hull, propeller and rudder with low resistance, high efficiency and appropriate propeller light running margin. The models were tested in the towing tank to verify the speed performance of the two sets of hulls, propellers and rudders. It was found that the ship integration optimization method based on the fully-parametric model excavated the improvement space of the ship’s speed performance from the overall level and realized the integration optimization of the fully-parametric model. The design of hull, propeller and rudder achieved the best speed performance. Compared with the initial design, the speed performance was greatly improved. By analyzing the effects of the hull, propeller and rudder separately, it was found that these parts have different effects on speed performance improvement, and ultimately can maximize the overall comprehensive income; CFD calculation and model test results had a good agreement.

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

A dynamic modeling approach to predict water inflow during tunnel excavation in relatively uniform rock masses - Zhongxia Li; Jing Xiao; Junwei Wan; Jianmei Cheng; Haibo Feng; Hongbin Zhan; Shuai Yuan; Kun Huang (Tunnelling and Underground Space Technology, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Application of Italian ryegrass residue changes the soil biochemical properties and bacterial communities in Southern China - Yao Xiang; Mengyan Cao; Hongbin He; Yu Song; Cheng Jin; Guorong Xin; Chuntao He (Applied Soil Ecology, 2024)

Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

2D flake-like garnet electrolytes for solid-state lithium metal batteries - Jun Cheng; Yixuan Guo; Hongqiang Zhang; Fengjun Ji; Xuan Zhou; Zhen Zeng; Hongbin Liu; Qing Sun; Deping Li; Lijie Ci (Chemical Engineering Journal, 2024)

Italian ryegrass (Lolium multiflorum L.)-rice (Oryza sativa L.) rotation promotes the nitrogen cycle in the rice rhizosphere through dominant ammonia-oxidizing bacteria - Mengyan Cao; Yao Xiang; Hongbin He; Junkang Cheng; Yu Song; Cheng Jin; Guorong Xin; Chuntao He (Applied Soil Ecology, 2024)

Graphene-based photocatalysts for degradation of organic pollution - Yuxi Zhang; Kuangjun Li; Meng Zang; Yuanyuan Cheng; Hongbin Qi (Chemosphere, 2023)

Low concentration chlorantraniliprole-promoted Ca2+ release drives a shift from autophagy to apoptosis in the silk gland of Bombyx mori - Haoyi Gu; Qilong Shu; Minli Dai; Hongbin Zou; Yuanfei Wang; Jialu Cheng; Yue Su; Fanchi Li; Bing Li (Pesticide Biochemistry and Physiology, 2023)

Preharvest glycerol treatment enhances postharvest storability of orange fruit by affecting cuticle metabolism - Zhifeng Zhu; Wanjun Mei; Ruixue Li; Huan Liu; Shuying Chen; Hongbin Yang; Rangwei Xu; Taojiang Huang; Jingsong Xiang; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2023)

Emergence of novel tigecycline resistance gene tet(X5) variant in multidrug-resistant Acinetobacter indicus of swine farming environments - Yumeng Cheng; Yakun Li; Meng Yang; Yang He; Xinru Shi; Zhidan Zhang; Yesheng Zhong; Yuan Zhang; Hongbin Si (Veterinary Microbiology, 2023)

Northern high-latitude sea ice variation linked with East Asian monsoon anomalies during the Younger Dryas - Xiaolong Chen; Hongbin Zhang; Michael L. Griffiths; Xiaogui Peng; Liangzhe Yang; Ming Yu; Junhua Huang; Shuyu Xue; Hai Cheng; Shuai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A feruloyl esterase/cellulase integrated biological system for high-efficiency and toxic-chemical free isolation of tobacco based cellulose nanofibers - Mengxing Zhao; Xingye An; Zhongqiu Fan; Shuangxi Nie; Zhengbai Cheng; Haibing Cao; Xiaohong Zhang; Md Manik Mian; Hongbin Liu; Liqin Liu (Carbohydrate Polymers, 2023)

Hypoxia and warming take sides with small marine protists: An integrated laboratory and field study - Cheng Qian; Kailin Liu; Mengwen Pang; Zhimeng Xu; Lixia Deng; Hongbin Liu (Science of The Total Environment, 2023)

Interpenetrating network expansion sponge based on chitosan and plasma for ultrafast hemostasis of arterial bleeding wounds - Yuting Shi; Wenwen Yu; Xiaoqin Liang; Ju Cheng; Yufei Cao; Mingsheng Liu; Yu Fang; Zheng Yang; Hongbin Liu; Hua Wei; Guanghui Zhao (Carbohydrate Polymers, 2023)

Durable, breathable, sweat-resistant, and degradable flexible sensors for human motion detection - Min Guan; Yang Liu; Hong Du; Yinying Long; Xingye An; Hongbin Liu; Bowen Cheng (Chemical Engineering Journal, 2023)

Understanding the versatile roles of cellulose nanocrystals in α-amylase immobilization, starch hydrolysis, colloidal stability and printability towards advanced starch based bio-latex performance - Liqin Liu; Xingye An; Xiaohong Zhang; Zhengbai Cheng; Jinhuan Guo; Shuangxi Nie; Haibing Cao; Hongbin Liu; Yonghao Ni (Chemical Engineering Journal, 2023)

Highly graphitized lignin-derived porous carbon with hierarchical N/O co-doping “core-shell” superstructure supported by metal-organic frameworks for advanced supercapacitor performance - Yinying Long; Xingye An; Hao Zhang; Jian Yang; Liqin Liu; Zhongjian Tian; Guihua Yang; Zhengbai Cheng; Haibing Cao; Hongbin Liu; Yonghao Ni (Chemical Engineering Journal, 2023)

Reconfigurable origami-inspired window for tunable noise reduction and air ventilation - Xiaomeng Jin; Hongbin Fang; Xiang Yu; Jian Xu; Li Cheng (Building and Environment, 2023)

Buffer effect of MgO on Na2SO3 to stabilize S(IV) for the enhancement in simultaneous absorption of NOx and SO2 from non-ferrous smelting gas - Wenjun Huang; Sichao Li; Hongbin Wang; Peng Cui; Haomiao Xu; Can Cheng; Zan Qu; Naiqiang Yan (Environmental Science and Pollution Research, 2022)

CitWRKY28 and CitNAC029 promote the synthesis of cuticular wax by activating CitKCS gene expression in citrus fruit - Hongbin Yang; Zhifeng Zhu; Mingfei Zhang; Xin Li; Rangwei Xu; Feng Zhu; Juan Xu; Xiuxin Deng; Yunjiang Cheng (Plant Cell Reports, 2022)

Synthesis and biological activity of amide derivatives derived from natural product Waltherione F - Hongbin Fang; Zhanfang Chen; Xuewen Hua; Wenrui Liu; Chenmeng Xue; Yi Liu; Xiaohe Zhu; Man Yuan; Shuang Cheng; Bingxiang Wang; Jing Ru; Dzmitry Bazhanau; et al. (Medicinal Chemistry Research, 2022)

Study of Heavy Metals and Microbial Communities in Contaminated Sediments Along an Urban Estuary - Jun Yi; Linus Shing Him Lo; Hongbin Liu; Pei-Yuan Qian; Jinping Cheng (Frontiers in Marine Science, 2021)
Estuarine sediments are increasingly contaminated by heavy metals as a result of urbanization and human activities. Continuous multi-heavy metal accumulation in the ecosystem can provoke new effects on top of the complex environmental interactions already present in estuarine ecosystems. It is important to study their integrated influence on imperative microbial communities to reflect on the environmental and ecological risks they may impose. Inductively coupled plasma optical emission spectroscopy analysis for five metals Cd, Cr, Cu, Pb, and Zn showed that Cr and Cu concentrations in intertidal sediments of the urbanized Yangtze River estuary in China have consistently exceeded respective threshold effect concentration (TEC) levels. The geo-accumulation and potential ecological risk index results of the five metals showed that all sampling sites were weakly to moderately polluted, and at considerable to high ecological risk, respectively. Redundancy and correlation analyses showed that Zn followed by Cr in the ecosystem were explanatory of the shifts in recorded microbial community structures. However, the spatial variation in metal concentrations did not correspond to the selection of metal resistance genes (MRGs). Unlike many other dominant bacterial taxa, most of the sulfate-reducing bacteria (SRB) and associated sulfate respiration as the dominant microbially contributed ecological function were found to negatively correlate with Zn and total heavy metal pollution. Zn concentration was proposed to be a potent indicator for heavy metal pollution-associated microbial community compositional shifts under urbanized estuarine conditions. The associations between heavy metals and estuarine microbial communities in this study demonstrate the influence of heavy metals on microbial community structure and adaptations that is often overshadowed by environmental factors (i.e., salinity and nutrients).

Citrus NIP5;1 aquaporin regulates cell membrane water permeability and alters PIPs plasma membrane localization - Mingfei Zhang; Ruilian Liu; Hai Liu; Hongbin Yang; Xin Li; Ping Wang; Feng Zhu; Rangwei Xu; Shaowu Xue; Yunjiang Cheng (Plant Molecular Biology, 2021)

Snapshot of Peptidomics of the Red Tide Forming Species Noctiluca scintillans - Shuwen Zhang; Cheng Li; Shunyan Cheung; Mingming Sun; Shuqun Song; Wang Guo; Cui Guo; Gongguo Wu; Hongbin Liu (Frontiers in Marine Science, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

PB2 and hemagglutinin mutations confer a virulent phenotype on an H1N2 avian influenza virus in mice - Zhijun Yu; Zhiguang Ren; Yongkun Zhao; Kaihui Cheng; Weiyang Sun; Xinghai Zhang; Jiaqiang Wu; Hongbin He; Xianzhu Xia; Yuwei Gao (Archives of Virology, 2019)

Continuous efficient removal and inactivation mechanism of E. coli by bismuth-doped SnO2/C electrocatalytic membrane - Pengfei Wang; Yu Deng; Limei Hao; Lei Zhao; Xinqi Zhang; Cheng Deng; Hongbin Liu; Mengfu Zhu (Environmental Science and Pollution Research, 2019)

Inhibition of P2X7 receptors improves outcomes after traumatic brain injury in rats - Xiaofeng Liu; Zhengqing Zhao; Ruihua Ji; Jiao Zhu; Qian-Qian Sui; Gillian E. Knight; Geoffrey Burnstock; Cheng He; Hongbin Yuan; Zhenghua Xiang (Purinergic Signalling, 2017)

Quality analysis, classification, and authentication of liquid foods by near-infrared spectroscopy: A review of recent research developments - Lu Wang; Da-Wen Sun; Hongbin Pu; Jun-Hu Cheng (Critical Reviews in Food Science and Nutrition, 2017)

A modified protocol for the detection of three different mRNAs with a new-generation in situ hybridization chain reaction on frozen sections - Qian-qian Sui; Jiao Zhu; Xiangnan Li; Gillian E. Knight; Cheng He; Geoffrey Burnstock; Hongbin Yuan; Zhenghua Xiang (Journal of Molecular Histology, 2016)

Comparing Four Dimension Reduction Algorithms to Classify Algae Concentration Levels in Water Samples Using Hyperspectral Imaging - Hongbin Pu; Lu Wang; Da-Wen Sun; Jun-Hu Cheng (Water, Air, & Soil Pollution, 2016)

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Use of multi-objective dredging for remediation of contaminated sediments: a case study of a typical heavily polluted confluence area in China - Cheng Liu; Shiguang Shao; Qiushi Shen; Chengxin Fan; Qilin Zhou; Hongbin Yin; Fuliu Xu (Environmental Science and Pollution Research, 2015)

Up-regulation of P2X7 receptors mediating proliferation of Schwann cells after sciatic nerve injury - Xian-min Song; Xiao-hui Xu; Jiao Zhu; Zhili Guo; Jian Li; Cheng He; Geoffrey Burnstock; Hongbin Yuan; Zhenghua Xiang (Purinergic Signalling, 2015)

Experimental infection of dogs with H6N1 avian influenza A virus - Kaihui Cheng; Zhijun Yu; Yuwei Gao; Xianzhu Xia; Hongbin He; Yuping Hua; Hongliang Chai (Archives of Virology, 2014)

Block of P2X7 receptors could partly reverse the delayed neuronal death in area CA1 of the hippocampus after transient global cerebral ischemia - Qiang Yu; Zhili Guo; Xiaofeng Liu; Qing Ouyang; Cheng He; Geoffrey Burnstock; Hongbin Yuan; Zhenghua Xiang (Purinergic Signalling, 2013)